A review of studies of childhood cancer and natural background radiation. (3rd June 2021) - Kendall, Gerald M.; Little, Mark P.; Wakeford, Richard
Abstract: Purpose: The projected existence and magnitude of carcinogenic effects of ionizing radiation at low doses and low-dose rates is perhaps the most important issue in radiation protection today. Studies of childhood cancer and natural background radiation have the potential to throw direct light on this question, into a dose range below a few tens of mSv. This paper describes the studies that have been undertaken and their context, discusses some problems that arise and summarizes the present position. Conclusions: Many such studies have been undertaken, but most were too small to have a realistic chance of detecting the small effects expected from such low doses, based on risk projections from higher exposures. Case–control or cohort studies are to be preferred methodologically to ecological studies but can be prone to problems of registration/participation bias. Interview-based studies of the requisite size would be prohibitively expensive and would undoubtedly also run into problems of participation bias. Register-based studies can be very large and are free of participation bias. However, they need to estimate the radiation exposure of study subjects using models rather than individual measurements in the homes of those concerned. At present, no firm conclusions can be drawn from the studies that have been published to date. Further data and perhaps pooled studies offer a way forward.